Utilizing Consumer Perception of Edamame to Guide New Variety Development - Carneiro, Renata; Duncan, Susan; O'Keefe, Sean; Yu, Dajun; Huang, Haibo; Yin, Yun; Neill, Clinton; Zhang, Bo; Kuhar, Thomas; Rideout, Steve; Reiter, Mark; Ross, Jeremy; et al. (Frontiers in Sustainable Food Systems, 2021)
Consumption of edamame (vegetable soybeans) has increased significantly in the U.S. over the last 20 years. Although market demand has been increasing, most edamame is still imported from Asian countries. A team of multistate plant-breeding programs in the mid-Atlantic and Southeast U.S. has focused on developing new breeding lines that grow well in the U.S. and deliver what domestic growers, processors and consumers need and expect from their edamame. In our study, sensory evaluation was used to identify edamame genotypes and sensory attributes preferred by consumers to support breeding selection criteria. In the first year (reported as our “screening study”), 20 edamame genotypes were grown in three locations: Newport, AR, and Blacksburg and Painter, VA. In the second year (reported as our “validation study”), 10 edamame genotypes selected after our screening study were grown in Blacksburg and Painter, VA, Portageville, MO, and Stoneville, MS. In both years of research, untrained participants (adults; vegetable consumers not allergic to soy; N ≥ 50) used a traditional 9-point acceptability (hedonic) scale (1 = “dislike extremely”; 9 = “like extremely”) to evaluate overall-liking, aroma, appearance, taste, and texture, and a 5-point scale (1 = “not sweet,” 5 = “extremely sweet”) to evaluate sweetness intensity. Next, participants used a check-all-that-apply (CATA) list of selected sensory terms to describe the sensory characteristics of each edamame sample. Overall acceptability of edamame genotypes was significantly different among all genotypes (p < 0.05). Samples described as “bitter,” “sour” (flavor) or “starchy” (texture) were associated with lower acceptability scores while “salty” and “sweet” (flavor) were correlated with higher acceptability. Sensory data from the screening study were used to select the best genotypes by use of a defined decision process based on the consumer data. The validation study tested the selection decisions and further supported the genotype choices. Sensory evaluation is a powerful tool to direct breeders to improve market acceptability and develop new edamame genotypes. Both screening and validation studies illustrate the significant role of consumer sensory data in support of genotypes targeted for domestic (U.S.) production.